Application of improved Lotka-Volterra model differential equations for exploring plant species interactions in arid regions - Hu, Zhijie; Xu, Jiantao; Wang, Yiming; Yun, Lijia; Luo, Run; Wei, Tianjie (SPIE, 2024)
In ecosystems, the extent to which plants benefit from biodiversity to adapt to drought is influenced by interactions between the environment and plant populations. In this paper, a plant community interaction model based on an improved LotkaVolterra competition model is established. The model analyzes various factors influencing plant drought tolerance from a community perspective, thereby further elucidating the importance of biodiversity. We initially construct a basic LotkaVolterra model using four plant species as subjects and run and validate the model. Then, trigonometric functions are introduced to explore variations in weather factors, synthesizing the impacts of environmental temperature and humidity through normalization indices. We also endeavor to handle more complex ecosystems by attempting to increase the number of species and alter species types. In addition, environmental influences on species, such as habitat reduction due to environmental pollution and human activities, are considered, introducing corresponding impact factors. Finally, our research indicates that the frequency and amplitude of drought events significantly affect the diversity and viability of plant communities. The degree of environmental pollution and habitat alterations also alter the stability and species diversity of plant communities. The improved Lotka-Volterra model can be used to explore plant relationships in complex arid environments.